2017
DOI: 10.4236/ojst.2017.75022
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Impacted Maxillary Canines in a Palestinian Population: A Retrospective Study

Abstract: Objective: This study aims to estimate the prevalence of impacted maxillary canines using panoramic radiographs. Methods: A sample of 1321 panoramic radiographs were retrospectively examined for the presence of impacted maxillary canines. The radiographs were obtained from the records of a private dental clinic from the year 2009 till 2016. Results: The prevalence of impacted canines among the examined population (n = 1321) was found to be 1.8%. There was a significant association between gender and canine imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…However, no significant difference in the prevalence of right or left canine impaction in the analysed data. These findings were consistent with other researchers [14,22]. Yet, different results from other studies reporting different distribution of unilaterally impacted maxillary canines between the left and right sides [9,20].…”
Section: Disscusionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, no significant difference in the prevalence of right or left canine impaction in the analysed data. These findings were consistent with other researchers [14,22]. Yet, different results from other studies reporting different distribution of unilaterally impacted maxillary canines between the left and right sides [9,20].…”
Section: Disscusionsupporting
confidence: 92%
“…However, other found that the most affected side was the right side in both males and females [19,21]. In general, the results of this study agree with most studies that investigated the impaction of maxillary canines regarding females, unilateral impaction, and non-dominance of the side of maxillary canine impaction [14,21,23].…”
Section: Disscusionsupporting
confidence: 89%
See 1 more Smart Citation
“…Arandi et al [ 26 ] investigated the prevalence of impacted maxillary canines on panoramic radiographs of 1321 Palestinian individuals aged between 15 and 67 and found a statistically significant relationship between gender and canine impaction. Accordingly, females have a higher incidence of impacted canines than males.…”
Section: Discussionmentioning
confidence: 99%
“…Canines that are only partially erupted or impacted that are left untreated can lead to several complications. These issues include dental arch shortening, follicular cyst formation (Dentigerous cysts), canine tooth ankylosis, recurring infections, discomfort, internal resorption, external resorption of the canine and surrounding teeth, or a combination of these [12,13] . As a result, a more precise diagnosis and treatment plan can be developed, reducing the risk of problems related to the disease's occurrence or treatment [14] .…”
Section: Introductionmentioning
confidence: 99%